Detection of rest-frame optical lines from x-shooter spectroscopy of weak emission-line quasars - Plotkin, Richard; Shemmer, O.; Trakhtenbrot, B.; Anderson, S.; Brandt, W.; Fan, X.; Gallo, E.; Lira, P.; Luo, B.; Richards, G.; Schneider, D.; Strauss, M.; et al. (Institute of Physics Publishing, 2015)
Over the past 15 yr, examples of exotic radio-quiet quasars with intrinsically weak or absent broad emission line regions (BELRs) have emerged from large-scale spectroscopic sky surveys. Here, we present spectroscopy of seven such weak emission line quasars (WLQs) at moderate redshifts (z = 1.4-1.7) using the X-shooter spectrograph, which provides simultaneous optical and near-infrared spectroscopy covering the rest-frame ultraviolet (UV) through optical. These new observations effectively double the number of WLQs with spectroscopy in the optical rest-frame, and they allow us to compare the strengths of (weak) high-ionization emission lines (e.g., C iv) to low-ionization lines (e.g., Mg ii, Hß, H) in individual objects. We detect broad Hß and H emission in all objects, and these lines are generally toward the weaker end of the distribution expected for typical quasars (e.g., Hß has rest-frame equivalent widths ranging from 15-40). However, these low-ionization lines are not exceptionally weak, as is the case for high-ionization lines in WLQs. The X-shooter spectra also display relatively strong optical Fe ii emission, Hß FWHM ? 4000 km s-1, and significant C iv blueshifts (˜1000-5500 km s-1) relative to the systemic redshift; two spectra also show elevated UV Fe ii emission, and an outflowing component to their (weak) Mg ii emission lines. These properties suggest that WLQs are exotic versions of "wind-dominated" quasars. Their BELRs either have unusual high-ionization components, or their BELRs are in an atypical photoionization state because of an unusually soft continuum. © 2015. The American Astronomical Society. All rights reserved.